Current perspectives on literary reading - Escandell, Dari; Rovira-Collado, José (IVITRA research in linguistics and literature ;, 2019)
"This collection aims to provide answers regarding what the most recent trends are in research in literary reading. Based on that premise, it contains a rigorously selected and varied roster of investigations that focus on presenting and attempting to interpret and understand the most recent literary trends or tendencies, as well as the reasons for the propensities they create among the masses of young and adult readers. This selection of texts in English, Catalan and Spanish will give the reading specialist an idea of where today's trends are headed, and how they point towards the formation of a new paradigm in matters of literature"--